2017
DOI: 10.1371/journal.pone.0176351
|View full text |Cite|
|
Sign up to set email alerts
|

Management of vertebral compression fracture in general practice: BEACH program

Abstract: ImportanceThe pain associated with vertebral compression fractures can cause significant loss of function and quality of life for older adults. Despite this, there is little consensus on how best to manage this condition.ObjectiveTo describe usual care provided by general practitioners (GPs) in Australia for the management of vertebral compression fractures.Design, setting and participantsData from the Bettering the Evaluation And Care of Health (BEACH) program collected between April 2005 and March 2015 was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Megale and colleagues [24] reported that the most common reason for driving medical care seeking behavior is surprisingly not back pain (48%) but an experience of trauma or injury (6%), a past diagnosis of fracture (6%), or a complaint of not being able to sleep. Emotionally, patients with a history of VF or VA may seek medical care once back pain is recurrent, but no correlation was found between the timing for seeking medical aid and history of VF or VA in this cohort of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Megale and colleagues [24] reported that the most common reason for driving medical care seeking behavior is surprisingly not back pain (48%) but an experience of trauma or injury (6%), a past diagnosis of fracture (6%), or a complaint of not being able to sleep. Emotionally, patients with a history of VF or VA may seek medical care once back pain is recurrent, but no correlation was found between the timing for seeking medical aid and history of VF or VA in this cohort of patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is frequently prescribed as an analgesic and antipyretic in the treatment of headache, toothache, migraine, dysmenorrhea, myalgia, neuralgia, musculoskeletal, tonsillectomy pain, the common cold, influenza, and other bacterial and viral infections. It can also be used as a pain controller for numerous cases in neurosurgery and emergency departments, including posterior lumbar laminectomy ( 24 ), vertebral compression fractures ( 25 ), spinal primary and metastatic tumors ( 26 ), post-craniotomy in intracranial pathology surgery ( 27 ), traumatic fractures of bones ( 28 ), urinary colic ( 29 ) and acute appendicitis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even with such devastating numbers, many individuals with vertebral fractures continue to go unnoticed and are never diagnosed and therefore never treated, or treated too late, for the underlying osteoporosis. This might be due to diffuse and low symptom burden for the patient, making it assessed as an age-related differential diagnosis [2, 5, 13, 37].…”
Section: Discussionmentioning
confidence: 99%